A longitudinal study on the lexical sophistication and sentence length in Finnish upper secondary school students’ English compositions. - Reiman, Iida (My University, 2016)
The aim of the present study was to find out the level of lexical sophistication and the mean length of sentences used in compositions written by Finnish upper secondary school students of English. In addition, the present study investigated the possible relationship between the two abovementioned variables. The study at hand was longitudinal: as data, a set of 50 compositions were collected in 2014 from the same writers both in the first and the final year of upper secondary school, 25 in the first year and 25 in the final year. In the analysis, an internet-based program called VocabProfile was utilized in order to find out the lexical sophistication of the investigated students. To find out the mean length of sentence and the relationship between these two, I used Microsoft Excel. Findings of the present study include a minor decrease in the use of less frequent vocabulary and a slight increase in the use of the two most frequently appearing thousand words of English: both of these changes were 1.99 percentage points. As for the mean length of sentence, it grew by 1.28 words during upper secondary school. As for the relationship between the two variables, no clear correlations could be found. It became, however, relatively clear that the topic of the composition might have an effect on the results. Thus more research is needed to fully see the effect of lexical sophistication and mean length of sentence on one another. In addition, future research would benefit greatly if all investigated students wrote on the same topic.